Seismic retrofitting: Learning from vernacular architecture - Lourenço, Paulo B. (2015)
Local communities have adapted for centuries to challenging surroundings, resulting from unforeseen natural hazards. Vernacular architecture often reveals very intelligent responses attuned to the environment. Therefore, the question that emerged was: how did local populations prepare their dwellings to face frequent earthquakes? It was to respond to this gap in knowledge, that the SEISMIC-V research project was instigated, and this interdisciplinary international publication was prepared. The research revealed the existence of a local seismic culture, in terms of reactive or preventive seismic resistant measures, able to survive, if properly maintained, in areas with frequent earthquakes. The fundamental contribution and aims of the publication were to enhance: -The disciplinary interest in vernacular architecture; -Its contribution to risk mitigation in responding to natural hazards; -To encourage academic and scientific research collaboration among different disciplines; -To contribute to the improvement of vernacular dwellings, which half of the world’s population still inhabits nowadays. Fifty international researchers and experts presented case studies from Latin America, the Mediterranean, Eastern and Central Asia and the Himalayas region, with reference to 20 countries, i.e. Algeria, Bolivia, Bhutan, Chile, China, Egypt, El Salvador, Greece, Haiti, Italy, Japan, Mexico, Morocco, Nepal, Nicaragua, Peru, Romania, Taiwan, Turkey and a closer detailed analysis of Portugal. This publication brings together 43 contributions, with new perspectives on seismic retrofitting techniques and relevant data, addressing vernacular architecture; an amazing source of knowledge, and to this day, home to 4 billion people.